2017
DOI: 10.1371/journal.pone.0180892
|View full text |Cite
|
Sign up to set email alerts
|

Secretory carrier membrane protein 5 is an autophagy inhibitor that promotes the secretion of α-synuclein via exosome

Abstract: Autophagy-lysosomal pathway is a cellular protective system to remove aggregated proteins and damaged organelles. Meanwhile, exosome secretion has emerged as a mode to selectively clear the neurotoxic proteins, such as α-synuclein. Mounting evidence suggests that these two cellular processes are coordinated to facilitate the clearance of toxic cellular waste; however the regulators for the transition between these two processes are unclear. Here we show that SCAMP5, a secretory carrier membrane protein signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 43 publications
3
49
0
Order By: Relevance
“…In vitro experiments using bafilomycin A (autophagy inhibitor, by preventing the fusion of autophagosome with lysosome) treatment resulted in impaired autophagic flux, as demonstrated by significant cellular accumulation of p62. We demonstrated that blocking the fusion of autophagosomes and lysosomes inhibits autophagic flux and promotes exosome secretion, as an alternative mechanism for the clearance of toxic proteins; our results are consistent with a recent study . Collectively, our results suggest that chronic alcohol administration affects lysosomes, thus disrupting autophagosome and lysosome fusion and exosome secretion.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In vitro experiments using bafilomycin A (autophagy inhibitor, by preventing the fusion of autophagosome with lysosome) treatment resulted in impaired autophagic flux, as demonstrated by significant cellular accumulation of p62. We demonstrated that blocking the fusion of autophagosomes and lysosomes inhibits autophagic flux and promotes exosome secretion, as an alternative mechanism for the clearance of toxic proteins; our results are consistent with a recent study . Collectively, our results suggest that chronic alcohol administration affects lysosomes, thus disrupting autophagosome and lysosome fusion and exosome secretion.…”
Section: Discussionsupporting
confidence: 92%
“…We demonstrated that blocking the fusion of autophagosomes and lysosomes inhibits autophagic flux and promotes exosome secretion, as an alternative mechanism for the clearance of toxic proteins; our results are consistent with a recent study. (39) Collectively, our results suggest that chronic alcohol administration affects lysosomes, thus disrupting autophagosome and lysosome fusion and exosome secretion. Autophagy-exosome crosstalk is a complex and context-dependent process.…”
Section: Discussionmentioning
confidence: 73%
“…secretory carrier membrane protein 5, an autophagy flux inhibitor (Yang et al . ), was down‐regulated in the HIP (86.8%). Furthermore, we assayed the levels of other autophagy markers including LC3II (autophagosome formation), ATG5 (autophagosome elongation), and Beclin1 (autophagosome nucleation) by western blotting, all of which were clearly increased in the HIP and AMY (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the top 10, 9 were found to be increased in HET versus WT. Four of these genes have previously been associated to α-synuclein pathology: TMEM230 [58], TMEM175 [41], B4GALNT1 [96] and SCAMP5 [100]. TMEM230 gene product is involved in the trafficking of synaptic vesicles and retromer components [49] and mutations in this gene have been linked to autosomal dominant PD [19].…”
Section: Age-dependent Neurodegeneration In the Dorsal Striatum But Nmentioning
confidence: 99%
“…Thus, the increase of B4GALNT1 and TMEM175 in 3M HET mice may indicate an attempt to counteract abnormal α-syn. SCAMP5 has been shown to modulate calcium-dependent exocytosis by interactng with SNAREs [108] and α-syn secretion via exomes in vitro [100]. The gene products of two DEGs, measured in blood, have been reported to be associated with PD: PSMC4 (26S proteasome AAA-ATPase subunit Rpt3, a component of the proteasome complex) [69] and COPZ1 (COPI coat complex subunit zeta 1, encoding a subunit of the cytoplasmic coatamer protein complex, which is involved in autophagy and intracellular protein trafficking) [79].…”
Section: Age-dependent Neurodegeneration In the Dorsal Striatum But Nmentioning
confidence: 99%